Contemporary Indonesia and Asean in the post Covid-19 - Zarina Othman,; Bakri Mat,; Muhammad Danial Azman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In Volume 4, Issue 1, July 2024, SINERGI takes the readers to explore some of the most important security-related issues in Southeast Asia. In particular, the discussion focuses on Indonesia, one of the countries with the fastest-growing economy in the region. Indonesia has a dense population and ranks fourth in the world. Its new capital, Nusantara, is expected to attract more foreign investors for its development. Nevertheless, Indonesia has not been hit by domestic and international issues, especially in the post-COVID-19 era, such as the threat of energy consumption and conservation, terrorism, and unrest in Myanmar. The pandemic shows the fragility of the country and the region. Moreover, it demonstrates the importance of understanding health issues and their relation to security. Nevertheless, as presented by the authors in this volume, Indonesia maintains good relations with economic powers in Asia including the People's Republic of China and the Republic of Korea.